Positive Lateral Flow Urine Lipoarabinomannan Assay (LF-LAM) Result in Detection of Active Tuberculosis - Sara Puspita; Dewi Kartika Turbawaty; Nina Tristina; Leni Lismayanti (Faculty of Medicine, Universitas Padjadjaran, 2021)
Lipoarabinomannan (LAM) is the main component of M. tuberculosis (MTB) wall as result of MTB degradation by macrophages in the human body. In patients with active TB and HIV co-infection, a decrease in antibody responses may be apparent that some of LAM may not be bound with antibodies. In this condition, LAM can pass through the normal glomerular basement membrane and can be detected in the urine. One laboratory examination for detecting LAM is the Lateral Flow Urine Lipoarabinomannan (LF-LAM) assay that uses urine as the sample. The purpose of this cross-sectional observational descriptive comparative study was to compare the positivity rate of LF-LAM examination results in active TB patients with and without HIV infection. Random urine samples were collected from patients diagnosed with active TB with and without HIV infection who visited Dr. Hasan Sadikin General Hospital Bandung from August to October 2020. The proportion between the group with HIV and group without HIV was analyzed with the Chi-Square test. Subjects were 52 patients, consisting of 25 (48%) subjects with HIV infection and 27 (52%) subjects without HIV infection. The positive LF-LAM results were found in 11 (21%) subjects, consisting of 9 (36%) subjects with HIV infection and 2 (7%) subjects without HIV infection, with p=0.012. In conclusion, the positivity rate of LF-LAM results is higher in active TB patients with HIV infection compared to those without HIV infection.